Enhancing learning through the multimodal teaching approach in Chinese-as-a-second language classrooms / Buai Chin Heng - Buai, Chin Heng (Universiti Teknologi MARA, Kedah, 2021)
In the 21st century, meaning making is a multimodal act and as such, in teaching and learning, multimodal perspectives need to be considered. Besides language, meanings in classroom discourse are conveyed through other semiotic resources like images, sound and the teacher’s body language such as facial expressions, gaze, gestures, and postures. This article aims to study how the various semiotic modes were used by National School Chinese Language teachers in Malaysia to construct interpersonal meanings, via the construction of the teacher’s roles and the handling of the teacher-student relationship, to promote learning amongst non-native speakers of Mandarin in Chinese as second language (CSL) classrooms. This research draws on theories developed by the School of Systemic Functional Linguistics (SFL) for the analytical framework. Classroom observations, interviews and video recordings were used to collect data for the present research. Participants in this study were four CSL teachers from four national primary schools in Selangor and 63 students who attended the Level 4 CSL course in the schools. Lessons in the four schools were observed, video recorded, and transcribed verbatim. Findings showed that teachers had effectively adopted the multimodal teaching approach, drawing attention to the roles of teachers, in particular, the handling of the relationship between teachers and students to promote language learning and acquisition. These findings suggest that interpersonal meaning is a critical factor that needs to be considered by a teacher. Many teaching instances that occurred in the classrooms showed the deployment and co-deployment of various semiotic resources in constructing interpersonal meaning to enhance teaching and learning. The findings of this study will benefit teachers of not only CSL classes but teachers of other disciplines, developers of teaching and learning programs as well as researchers in the field of multimodal discourse.